Protective effect of micheliolide against inflammation and oxidative stress in asthma through the MAPK/NF-κB signalling pathway - Jia Wang; Dan Han; Lina Han; Qinzhen Zhang; Shaozhuang Liu; Jiapeng Hu; Yunxiao Shang (World Allergy Organization Journal, 2025)
Background: Asthma involves oxidative stress imbalance and activation of the NLRP3 inflammasome. Micheliolide (MCL), a sesquiterpene lactone compound, has promising anti-inflammatory properties. However, its therapeutic potential in asthma remains unexplored. Objective: We aimed to investigate the therapeutic potential of MCL in asthma by elucidating the molecular mechanisms. Methods: MCL was administered to both an ovalbumin-induced asthmatic mouse model and an interleukin-4/tumour necrosis factor alpha-activated BEAS-2B cell line to evaluate its effects comprehensively on airway inflammation, oxidative stress, and NLRP3 inflammasome activation. Network pharmacology analysis was utilised to evaluate the intricate interactions between asthma and MCL. Additionally, we analyzed the expression levels of critical factors involved in the MAPK/NF-κB signalling pathway. Results: The results demonstrated that MCL effectively mitigated airway hyperresponsiveness in asthma, suppressed inflammation, alleviated oxidative stress, and inhibited NLRP3 inflammasome activation. Furthermore, MCL exhibited notable inhibitory effects on MAPK/NF-κB signalling. Importantly, the inhibitory impact of MCL on asthmatic inflammatory responses was partially reversed by an NF-κB agonist, substantiating that MCL exerts its effects on asthma through the MAPK/NF-κB signalling pathway. These findings highlight MCL as a potent therapeutic candidate for asthma and shed light on the underlying molecular mechanisms driving its therapeutic efficacy.